Biomimic underwater autonomous systems - Nickols, Francis Malcolm John. (2008)
Many types of robot were built under this research grant. Some underwater robots were built, but as time progressed the research was extended to include robots that were suited for land. However there was one underlying common theme in almost all the robots, which was that of emulating locomotion techniques as used in nature. This type of robot can be named ?reciprocating mass? or oscillating mass? robot.